Comprehensive composite materials - Kelly, Anthony; Zweben, Carl (Elsevier, 2000)
A multi-reference source spanning the whole composites science field, this text covers such topics as: fibre reinforcements and general theory of composites; polymer matrix composites; metal matrix composites; test methods, nondestructive evaluation and smart composites; and design and application.